STRATEGI PENGELOLAAN KELAS INOVATIF TERHADAP PENGURANGAN KETIMPANGAN LITERASI BERBANTUAN TEKNOLOGI DIGITAL SISWA KELAS 1 SD - Azkiya, Azza; Rukmawati, Rukmawati (LPPM Universitas Bina Bangsa, 2025)
This study aims to explain classroom management strategies implemented to reduce literacy inequality among first-grade students at SD Negeri Munggangsari. Literacy inequality remains a serious problem at the elementary school level, primarily due to differences in learning motivation, access to reading materials, and support from the learning environment. This study used a descriptive qualitative approach and collected data through semi-structured interviews with teachers and observations of classroom learning processes. The study findings revealed that the main strategy implemented by teachers was providing rewards, such as praise, stickers, and positions as